Memaksimalkan Pengelolaan Arsip untuk Efisiensi dan Efektivitas di Madrasah Tsanawiyah Al-Azhar Samarinda - Ananiah, Ananiah; Nurdiniyya, Yasinta Qur’aini; Sumarno, Sumarno (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This research is motivated by the management of archives, which includes classification, storage, utilization, borrowing, maintenance, and depreciation of archives at Madrasah Tsanawiyah Al-Azhar that has not been fully implemented. The study was conducted at Madrasah Tsanawiyah Al-Azhar Samarinda using qualitative research, describing the results in paragraph form. Data collection techniques included observation, interviews, and documentation. Data sources were the Headmaster, Administrative Head, and Administrative Staff of Madrasah Tsanawiyah Al-Azhar Samarinda. Data analysis techniques included data reduction, presentation, and conclusion drawing. The findings of this thesis indicate that archive management at Madrasah Tsanawiyah Al-Azhar Samarinda is being maximally implemented. This is due to incomplete facilities for archive management, such as archive cabinets, shelves, filing cabinets, and archive folders. Challenges in archive management include the lack of specialized staff or archivists, insufficient facilities and equipment for archive storage, the absence of dedicated storage space for archives, and limited knowledge among staff, leading to self-learning due to a lack of training in archiving. Efforts to overcome these challenges include hiring expert staff in archiving, providing complete equipment and tools, involving staff in archiving training or technical guidance, and increasing or adding dedicated storage space, especially for incoming and outgoing correspondence archives.